Exploring Smoking Habits and Influential Factors among Female School Students in Kathmandu - Basnet, Kumari; Aryal, Bhagwan; Khanal, Kalpana; Acharya, Dibya (International Research Journal of MMC, 2025)
This article presents a qualitative research study investigating the experiences and influencing factors of smoking among female school students in Kathmandu, Nepal. The principal author's observations prompted the research, aiming to identify why girls smoke despite societal stigma. The study utilized a descriptive narrative qualitative design, employing snowball sampling and semi-structured interviews with six students from two secondary schools in Kirtipur municipality in February-March 2024. Thematic analysis revealed key insights into the positive and negative experiences of smoking, as well as motivations such as peer pressure, relationship issues, loneliness, advertising influence, fashion, and family problems. Ultimately, the research highlights the complex interplay of social and environmental factors contributing to female tobacco use in the region. It is implied that adolescent girls are prone to smoking, therefore, they should be prioritized in tobacco cessation interventions in schools and communities, focusing on resilience, coping mechanisms, and health consequences. Easy sale of tobacco products to adolescents should be strictly monitored.